ANALISIS PEMAHAMAN KONSEP MATEMATIS MATERI BANGUN DATAR PADA SISWA KELAS III di SDN KOTA SERANG - Sellina Ayu Kusumaningrum; Heni Pujiastuti (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this research was to analyze the students' understanding of mathematical concepts about two-dimesional figures at the elementary school. This qualitative descriptive study involved 40 third grade students at one of the public elementary schools in Serang. An understanding of mathematical concepts in solving the problem of two-dimensional figures materials referred to 5 indicators, namely defining the concept in writing, identifying examples and non-examples, presenting a concept in the form of models, diagrams, and symbols, changing one form of representation to another, and recognizing the conditions that determine a concept. This research found that the percentage for defining the concept in writing was 37.5%, meaning that students were still not able to define the concept in writing. Then, the percentage for identifying examples and non-examples was 32.5% meaning that students were still not able to identify examples and non-examples. The percentage for presenting a concept in the form of models, diagrams, and symbols was 77.5%, meaning that students were able to present a concept in the form of models, diagrams, and symbols. After that, the percentage for changing one form of representation to another was 27.5%, meaning that students still could not change one form of representation to another. Finally, the percentage for recognizing the conditions that determine a concept was 72.5%, meaning that students were able to recognize the conditions that determined a concept.